Transformasi Standar Akuntansi Organisasi Nirlaba: Analisis Bibliometrik Evolusi Penelitian Akuntansi Yayasan dalam Perspektif ISAK 35 - Maharani, Deli; Arsih, Fania Juni; Fatrissia, Intan Natial; Ramdani, Marwa Fitri; Ahmadi, Aprizal; Khalidanallah, Cherlin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Nonprofit organizations play a significant role in supporting social development through activities in education, healthcare, religion, humanitarian services, and community development. Increasing demands for transparency and public accountability have encouraged nonprofit entities to adopt good governance practices and prepare financial reports in accordance with applicable standards, including the implementation of ISAK 35 in Indonesia. This study aims to analyze the development of nonprofit organization research and identify emerging trends, major themes, and future directions of literature related to accountability and financial reporting during the 2020–2026 period. A descriptive quantitative approach with bibliometric analysis was employed. Data were collected from the Scopus database using keywords related to nonprofit organizations. An initial search yielded 11,272 documents, which were subsequently filtered based on publication year, subject area, document type, keyword relevance, and publication language, resulting in 250 articles eligible for analysis. The data were analyzed using VOSviewer through network, overlay, and density visualizations. The findings reveal that nonprofit organizations represent the central theme, strongly connected to topics such as volunteering, organizational culture, government, donation intention, social enterprise, and policy implementation. Furthermore, the literature demonstrates a shift from traditional themes toward human resource management, policy implementation, organizational value creation, and professionalization. Overall, the study highlights the increasingly multidisciplinary nature of nonprofit organization research, emphasizing governance, accountability, sustainability, and organizational professionalism.